Criminal records, discrimination, and Aboriginal communities: Enhancing employment opportunities. Issue 4 (December 2022) - Naylor, Bronwyn; Heydon, Georgina
Criminal record checking is now widespread in Australia. Aboriginal people are disproportionately represented in the criminal justice system, for a range of reasons including historic levels of disadvantage due to colonisation. They are therefore disproportionately likely to be negatively affected by criminal record checking when seeking employment, when taking on community governance roles, when being considered as kinship carers and so on. At the same time, productive and rewarding employment, and engagement in governance roles, are vital aspects of Aboriginal people's participation, contribution and engagement across all parts of the Australian community. This article examines practices, protocols and experiences of employers, employment agencies and government organisations in Western Australia and the Northern Territory managing the potential impact of a criminal record on Aboriginal employment. The article identifies four fields that can give rise to good employment practice: Background Checking; Recruitment; Risk Management; and Support and Engagement.